2023
DOI: 10.1371/journal.pone.0263021
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-secreted TNF-α affects differentiation efficiency and viability of pluripotent stem cell-derived human dopaminergic precursors

Shirley D. Wenker,
María Isabel Farias,
Victoria Gradaschi
et al.

Abstract: Disease is a neurodegenerative disorder characterised by the progressive loss of dopaminergic cells of the substantia nigra pars compacta. Even though successful transplantation of dopamine-producing cells into the striatum exhibits favourable effects in animal models and clinical trials; transplanted cell survival is low. Since every transplant elicits an inflammatory response which can affect cell survival and differentiation, we aimed to study in vivo and in vitro the impact of the pro-inflammatory environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…To date, we have focused our analysis on the peripheral immune response to the product, however, as a neuronal therapy it is important also to consider the response of brain resident immune cells - the microglia. Further work to understand the interaction of RC17-NPCs with microglia will be important as previous studies have revealed that microglial activation can be detrimental to stem cell derived NPC product survival and differentiation in vivo 68 and have shown microglial infiltration in similar allografts post-mortem 69 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, we have focused our analysis on the peripheral immune response to the product, however, as a neuronal therapy it is important also to consider the response of brain resident immune cells - the microglia. Further work to understand the interaction of RC17-NPCs with microglia will be important as previous studies have revealed that microglial activation can be detrimental to stem cell derived NPC product survival and differentiation in vivo 68 and have shown microglial infiltration in similar allografts post-mortem 69 .…”
Section: Discussionmentioning
confidence: 99%